Establishing Vietnam National University, Hanoi (VNU) as a research university by promoting S&T activities - Xuan, Le Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
VNU is one of the major university centers in Vietnam which has set a goal to become a research university (2010). With those characteristics of the research-university model (mentioned in the paper Essential characteristics of research universities on the website of UNESCO) we can see that in a research university, S&T activities play an important role. By analyzing existing information on S&T activities in VNU, this paper is aimed to inform the current condition of VNU and what the necessary policies should be made to establish VNU to become a research university. Code: 13032201